2017
DOI: 10.1051/shsconf/20173402001
|View full text |Cite
|
Sign up to set email alerts
|

Cloud Computing Adoption in Organisations: Review of Empirical Literature

Abstract: This study reviews literature on cloud computing adoption in organisations to identify its influential factors and its operationalisation in prior literature. We classify the factors that influence the cloud computing adoption using the three contexts suggested by the Technology-Organisation-Environment (TOE) framework, namely, technology, organisation, and environment. The finding suggests that the influences of these factors vary across studies and most of the studies have operationalised cloud computing ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…This suggests that ICT adoption and growth are dependent on how businesses use cloud computing and information systems to automate business processes and store information in the cloud for simple retrieval. Cloud computing (Ahmed, 2020;Alharbi et al, 2016;Ali, 2020;Alkhater et al, 2017;Asiaei et al, 2019;Hassan et al, 2017;Hiran & Henten, 2019;Jianwen, 2019;Lynn et al, 2020;A. Mohamed & Anter, 2018;Ngongo et al, 2019;Priyadarshinee et al, 2017;Raut et al, 2017;Senarathna et al, 2018;Senyo et al, 2016;Skafi et al, 2020) A systematic literature review was done, as previously indicated.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that ICT adoption and growth are dependent on how businesses use cloud computing and information systems to automate business processes and store information in the cloud for simple retrieval. Cloud computing (Ahmed, 2020;Alharbi et al, 2016;Ali, 2020;Alkhater et al, 2017;Asiaei et al, 2019;Hassan et al, 2017;Hiran & Henten, 2019;Jianwen, 2019;Lynn et al, 2020;A. Mohamed & Anter, 2018;Ngongo et al, 2019;Priyadarshinee et al, 2017;Raut et al, 2017;Senarathna et al, 2018;Senyo et al, 2016;Skafi et al, 2020) A systematic literature review was done, as previously indicated.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, organizations applied IT governance to onpremises computing which included software that ran on computers located within the premises of the organizations. However, increasingly organizations are leveraging cloud computing for their IT needs to remain competitive and innovative [48]. Similar to on-premises computing, organizations can also apply IT governance to cloud computing since business value creation through IT and managing IT risks apply just as much to on-premises computing as it does to cloud computing.…”
Section: It Governance and Cloud Computingmentioning
confidence: 99%
“…Compliance is the main factor in the adoption of CC because the location of data is not known by the customer or may not have control over the location, which creates legal issues with regulatory and privacy laws [19,21]. Many European Union countries and the USA do not give permission to a certain type of data to be moved out of their countries.…”
Section: E Compliance and Physical Locationmentioning
confidence: 99%
“…Relative advantage is defined as "the degree to which an innovation is perceived as being better than the idea it supersedes" [22,14]. According to [21] organisations recognize the significant importance of relative advantages of cloud computing, such as in reducing IT costs, creating a competitive advantage, and enabling easier access to the information. In this research, the concept of relative advantage is used as the degree to which understand CC technology as being better than other computing paradigms.…”
Section: F Relative Advantagementioning
confidence: 99%